Validation of ground effect drone - Dela Cruz, Joseph Eliz Ferdinand (Nanyang Technological University, 2023)
The world as we know it today functions due to international trade and most of this trade is shipped by large and slow cargo ships. Ground effect vehicles (GEVs) have been proposed as cargo vehicles to replace these cargo ships due to their faster speed and better fuel efficiency. This study aims to evaluate the performance of a GEV through a series of tests conducted in a controlled environment (wind tunnel). Aerodynamic data including measurements of lift, drag, thrust, and other parameters will be tested, as well as an analysis of the vehicle's stability and control characteristics in both freestream and ground effect conditions. Ground effect enhancing technologies, were not used to see the improvements of baseline results from ground effect alone.